Work from home can be distracting: Exploring the moderation role of transformational leadership on teleworking and cyber-slacking - Mahadih Kyambade; Afulah Namatovu; Abdul Male Ssentumbwe; Monica Tushabe (Cogent Education)
This study examines the association between teleworking and cyber-slacking among lecturers in higher institutions of learning in Uganda. Further emphasis is to investigate the moderation role of transformational leadership on the association. Quantitative data was collected using self-administered questionnaires from 240 academic staff from higher institutions of learning from in Uganda. Data were analyzed using Process Macro version 3.2 to ascertain the moderation role of transformational leadership on the association between teleworking and cyber-slacking. The results indicate a significant positive association between teleworking and cyber-slaking. It also found out a negative significant association between transformational leadership and cyber-slacking. Furthermore, the study found out that transformational leadership moderates the association between teleworking and cyber-slacking. Institutions of higher learning should invest in leadership training programs aimed at developing transformational leadership competencies among academic and administrative leaders. These programs should focus on enhancing communication skills, fostering a supportive work environment, and promoting a culture of accountability and empowerment. Leaders should communicate clear expectations regarding teleworking arrangements, including performance standards, communication protocols, and acceptable internet use policies. The study is one of a kind and first to investigate the role of transformational leadership on the association between teleworking and cyber-slacking especially amongst institutions of higher learning putting emphasis on a developing nation like Uganda.